"El gorro frigio" (1888): estereotipos dramatúrgicos, renovación escénica y circuitos de difusión en un sainete lírico de Manuel Nieto - García Torres, Andrea (Cuadernos de Música Iberoamericana, 2018)
In 1888 it was the premiere of one of the most important works in the catalog of the composer Manuel Nieto Matán (1844-1915), the sainete lírico El gorro frigio. The success of this title is not related to the break with established standards in the repertoire of género chico, neither in the use of new practices, quite the opposite. Based on his experience as a composer, conductor and theatre manager, both him and his librettists agglutinate here a series of clichés, which constitute a guarantee into the commercialized theatre environment at the end of the Nineteenth-Century. This study questions the ideology commitment of the sainete, remarks the versatility of the work in a way to adapt to the new drama impositions in the early Twentieth-Century associated to its new release in 1907, and finally it examines the reiteration of the appearance of character of la morena Trinidad in the different Hispanic cultural environments.